2009
DOI: 10.1002/ibd.20833
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis for the treatment of refractory Crohnʼs disease: Results of an open-label pilot study

Abstract: In patients with moderate-to-severely active CD who were refractory to or intolerant of immunosuppressants and/or anti-TNF agents, ECP was well tolerated and induced clinical response (50%) and remission (25%) in patients. Most patients were able to maintain a response with continued treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
0
30
0
3
Order By: Relevance
“…dependent disease [48,49]. In a recent multicenter study including 28 patients with moderate to severe CD refractory to immunomodulators and/or TNF-antagonists, ECP treatment achieved a marked reduction in CD activity: 50% of patients responded and 25% were in remission [50]. …”
Section: Disclosure Statementmentioning
confidence: 99%
“…dependent disease [48,49]. In a recent multicenter study including 28 patients with moderate to severe CD refractory to immunomodulators and/or TNF-antagonists, ECP treatment achieved a marked reduction in CD activity: 50% of patients responded and 25% were in remission [50]. …”
Section: Disclosure Statementmentioning
confidence: 99%
“…Two uncontrolled case series have been published suggesting that extracorporealphotopheresis (ECP) can promote remission for a proportion of patients in the category of steroid and/or immunosuppressant intolerant or refractory CD [165,166] . The domain of ECP is Tcell mediated diseases, like Tcell lymphoma or acute or chronic graft vs host disease (GvHD).…”
Section: Extracorporealphotopheresismentioning
confidence: 99%
“…IL10, also known as cytokinesynthesis inhibitory factor, is a potent anti-inflammatory cytokine [171] . Abreu et al [165] observed in 28 patients with moderatetoseverely active CD (mean baseline CDAI 324) who were refractory to or intolerant of immunosuppressants and/ or antiTNF agents that ECP was well tolerated and induced clinical response (50%) and remission (25%) in patients with CD [165] . Reinisch confirmed these results in 31 CD patients, ECP permitted reduction or discontinuation in steroid dependent or refractory patients [166] .…”
Section: Extracorporealphotopheresismentioning
confidence: 99%
“…Mean C-reactive protein (CRP) declined and intestinal permeability in patients with ileal and ileocolonic Crohn's disease decreased after ECP. Recently, a phase II study investigating ECP in 28 patients with moderately active CD who were refractory or intolerant to immunosuppressants and/or anti-TNF agents was completed (112). ECP was performed twice weekly for 4 weeks then twice weekly every other week until week 12.…”
Section: Ecp Therapy In Crohn's Diseasementioning
confidence: 99%